Geographical influence on the bioactive properties of kelulut honey from cocoa farm environments in Sabah and Sarawak: Implications for standardization and medicinal applications - Mohammad Yadiy Fikriy Mahathir; Mohd Hafiz Abd Majid; Mohd Sani Sarjadi; Roslina Mohd Shah (Universiti Malaysia Sabah press, 2024)
Kelulut honey, produced by stingless bees in Malaysia's Sabah and Sarawak, is well-known for its high concentration of bioactive substances such as phenolic acids, flavonoids, enzymes, and vitamins, which contribute to its antioxidant, anti-inflammatory, antibacterial, and wound-healing capabilities. However, these bioactive properties might vary greatly depending on botanical origin, geographical location, and climatic circumstances, complicating standardisation for medicinal and nutritional purposes. The purpose of this study is to analyse Kelulut honey samples collected from three different geographic areas within Sabah and Sarawak's diverse cocoa farm environments—Kota Kinabalu, Kota Samarahan, and Lundu—in terms of total phenolic content (TPC), DPPH radical scavenging activity, and antioxidant activity (FRAP assay). Honey was gathered from six nests in Kota Kinabalu (L03, L04, L06, L07, L08, L10), three nests in Lundu (LDU01, LDU02, LDU03), and three nests in Kota Samarahan (SMN01, SMN02, SMN03). The study revealed that bioactive characteristics varied between locations, with the highest TPC in sample L03 (109.84 mg GAE/g) and the lowest in LDU01 (42.74 mg GAE/g). The FRAP values varied from 69.70 mg AAE/g in L04 to 51.40 mg AAE/g in LDU01. The highest DPPH activity was in L06 (15.63%), whereas the lowest was in SMN03 (8.92%). The observed heterogeneity poses problems to standardising Kelulut honey as a medicinal or nutritious product, but it also provides opportunity for targeted marketing and value addition. Honey from places with higher bioactive content might be advertised as having superior health advantages, notably antioxidant and anti-inflammatory characteristics. Furthermore, the study emphasises the need to protect natural habitats and implement sustainable agriculture in order to retain the quality of Kelulut honey. The findings of this study might help to lead the creation of region-specific health supplements and pharmaceutical goods, as well as provide economic advantages to local communities by promoting distinctive, high-quality honey variations.This study not only improves our understanding of the mechanisms determining Kelulut honey's bioactive characteristics, but it also offers up new possibilities for its use in health and nutrition.